Effectiveness of Implementing Complete Systematic Land Registration in Preventing Land Disputes in Majalengka Regency - Juliansyah Nugraha, Maulana Fajar (TABELLIUS: Journal of Law, 2025)
Abstract. This study aims to determine and analyze the implementation of Complete Systematic Land Registration in achieving legal certainty and the obstacles and solutions in the implementation of PTSL in Majalengka Regency. The type of data used is primary and secondary data obtained through interviews and literature studies. The research concludes: 1) The effectiveness of the implementation of the Complete Systematic Land Registration (PTSL) in preventing land disputes in Majalengka Regency has been effective, although there are several obstacles in it. As experienced by Mr. Irwan, after participating in the PTSL, finally the land boundary dispute with his neighbor can be resolved and legal certainty regarding land ownership between the disputing parties can be achieved. This shows that the author believes that PTSL can effectively prevent and resolve land disputes. The implementation of the Complete Systematic Land Registration Program (PTSL) which has been running effectively can be observed from the objectives to be achieved through the Complete Systematic Land Registration Program (PTSL). The objectives to be achieved in the Complete Systematic Land Registration Program (PTSL) are to accelerate the provision of legal certainty and legal protection of community land rights in a certain, easy, fast, smooth, safe, fair, equitable and open and accountable manner, so as to improve the welfare and prosperity of the community and the state economy, as well as reduce and prevent land disputes and conflicts. 2) Technically, the obstacles in the implementation of PTSL in Majalengka Regency are the unavailability of the parties from the related sub-districts, and in the field of land measurement and mapping which has not been comprehensively implemented. The solution is to conduct land measurement and mapping thoroughly in the village/sub-district area that has been designated as the activity location, both for registered land plots, improving the quality of registered land plots that have not been mapped, and unregistered land plots that are carried out systematically and completely grouped in one complete village/sub-district area. Keywords: Effectiveness; Land Disputes; PTSL.